Prospective Evaluation of Aspergillus fumigatus-Specific IgG in Patients With Cystic Fibrosis - Eschenhagen, Patience; Grehn, Claudia; Schwarz, Carsten (Frontiers in Cellular and Infection Microbiology, 2021)
Background: In Cystic Fibrosis (CF), the airways are often colonized by opportunistic fungi. The most frequently detected mould is Aspergillus fumigatus (Af). Af diseases are associated with significant morbidity and mortality. The most common clinical picture caused by Af is allergic bronchopulmonary aspergillosis (ABPA), triggered by an immunological reaction against Af. Af bronchitis and invasive aspergillosis rarely occur in CF as a result of spore proliferation. Since pulmonary mycoses and exacerbations by other pathogens overlap in clinical, radiological and immunological characteristics, diagnosis still remains a challenge. The search for reliable, widely available biomarkers for Af diseases is therefore still an important task today. Objectives: Af-specific IgG m3 is a broadly available biomarker. Sensitivity and specificity data are contradictory and differ depending on the study population. In our prospective study on pulmonary Af diseases in CF, we determined specific IgG m3 in order to test its suitability as a biomarker for acute Af diseases and as a follow-up parameter. Methods: In this prospective single center study, 109 patients with CF were screened from 2016 to 2019 for Af-associated diseases. According to diagnostic criteria, they were divided into four groups (control, bronchitis, ABPA, pneumonia). The groups were compared with respect to the level of Af-specific IgG (ImmunoCAP Gm3). 21 patients could be enrolled for a follow-up examination. Results: Of the 109 patients, 36 were classified as acute Af-disease (Af bronchitis, ABPA, Af pneumonia). Of these, 21 patients completed follow up-screening. The median Af-specific Gm3 was higher in the acute Af-disease groups. There was a significant difference in Af-specific IgG m3 compared to the control group without acute Af-disease. Overall, there was a large interindividual scattering range. In the follow up-screening, most patients showed a decrease in Af-specific Gm3. Conclusion: Af-specific IgG m3 shows a large interindividual variability and is therefore not a useful single biomarker for acute Af-associated diseases. Gm3 should only be interpreted alongside with other biomarkers. In our small cohort, it showed a decrease in the follow up-screenings, Therefore, due to its broad availability, it could be suitable as a follow-up and monitoring biomarker.